2000
DOI: 10.1002/(sici)1099-0682(200005)2000:5<1107::aid-ejic1107>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Mechanism of Hydroperoxide Activation by Investigation of Dynamic Processes in the Coordination Sphere of Seven-Coordinated Molybdenum Peroxo Complexes

Abstract: Seven‐coordinated molybdenum oxobisperoxo complexes with chelate nitrogen donors like pyrazolylpyridines are catalysts for the epoxidation of olefins. An NMR spectroscopic and quantumchemical study on the fluxionality of the chelate ligand proves that during this process partial ligand dissociation takes place. This gave rise to a detailed theoretical study on the activation of CH3OOH at the model complex (NH3)2MoO(O2)2 including dissociation of one of the ammonia ligands and proton transfer from the hydropero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…These seven-coordinate molybdenum peroxo complexes are active catalysts for the epoxidation of olefins with TBHP, especially when L is a neutral bidentate N,N-ligand such as a substituted pyrazolylpyridine [40,43,44]. Mechanistic studies have indicated that the oxidising agent coordinates to the Mo VI centre, undergoes a proton transfer to one of the peroxo ligands and is activated for oxygen transfer by g 2 -coordination [45]. A catalytic run carried out with the solid 2* under conditions equivalent to those used for the fresh catalyst precursor 2 (Table 2) revealed a similar performance for the oxidation of cyclooctene.…”
Section: Catalytic Performance Of 1-3 Using Tbhp As Oxidantmentioning
confidence: 99%
“…These seven-coordinate molybdenum peroxo complexes are active catalysts for the epoxidation of olefins with TBHP, especially when L is a neutral bidentate N,N-ligand such as a substituted pyrazolylpyridine [40,43,44]. Mechanistic studies have indicated that the oxidising agent coordinates to the Mo VI centre, undergoes a proton transfer to one of the peroxo ligands and is activated for oxygen transfer by g 2 -coordination [45]. A catalytic run carried out with the solid 2* under conditions equivalent to those used for the fresh catalyst precursor 2 (Table 2) revealed a similar performance for the oxidation of cyclooctene.…”
Section: Catalytic Performance Of 1-3 Using Tbhp As Oxidantmentioning
confidence: 99%
“…Due to the coordination of the oxidant, such as H 2 O 2 or tBuOOH, to the metal center and due to the high activation barriers for the stabilized complexes, these catalytic processes must involve different species formed in subsequent reaction steps. Thiel and co-workers recently gave experimental [13] and theoretical [17] evidence for a potential proton transfer from an alkyl hydroperoxide ligand ROOH that is coordinated to the metal center, to an η 2 -peroxo group of [MoO(η 2 -O 2 ) 2 (NH 3 )(ROOH)]. During intramolecular proton transfer, the metalladioxirane moiety M(O 2 ) is opened and species of the type [MoO(η 2 -O 2 )(η 1 -OOH)(NH 3 )(η 1 -OOR)] are formed.…”
Section: Vi) Influence Of Additional Ligands Lј At the Metal Centermentioning
confidence: 99%
“…[16] Note that, in the catalytic systems, the coordination of the oxidant such as hydrogen peroxide, silyl peroxides, or tert-butyl hydroperoxide to the metal center and subsequent proton transfer can yield different species which are potentially more reactive than the parent η 2 -peroxo complex. [10,13,17,21] Unless otherwise Scheme 3. Concepts for the control of reactivity of olefin oxidation with Mimoun-type peroxo complexes stated, transfer of the peroxo oxygen atom, which is located trans to the phosphane oxide, has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of kinetic, spectroscopic and theoretical studies, the authors provided a mechanism, whose key steps are sketched in Scheme 12. In this context a major role appears to be played by the fluxionality of the particular ligands used 157 .…”
Section: Momentioning
confidence: 99%